Genetic Analyses of Common Infections in the Avon Longitudinal Study of Parents and Children Cohort - Chong, Amanda H. W.; Mitchell, Ruth E.; Hemani, Gibran; Davey Smith, George; Yolken, Robert H.; Richmond, Rebecca C.; Paternoster, Lavinia (Frontiers in Immunology, 2021)
The burden of infections on an individual and public health is profound. Many observational studies have shown a link between infections and the pathogenesis of disease; however a greater understanding of the role of host genetics is essential. Children from the longitudinal birth cohort, the Avon Longitudinal Study of Parents and Children, had 14 antibodies measured in plasma at age 7: Alpha-casein protein, beta-casein protein, cytomegalovirus, Epstein-Barr virus, feline herpes virus, Helicobacter pylori, herpes simplex virus 1, influenza virus subtype H1N1, influenza virus subtype H3N2, measles virus, Saccharomyces cerevisiae, Theiler’s virus, Toxoplasma gondii, and SAG1 protein domain, a surface antigen of Toxoplasma gondii measured for greater precision. We performed genome-wide association analyses of antibody levels against 14 infections (N = 357 – 5010) and identified three genome-wide signals (P < 5×10-8), two associated with measles virus antibodies and one with Toxoplasma gondii antibodies. In an association analysis focused on the human leukocyte antigen (HLA) region of the genome, we further detected 15 HLA alleles at a two-digit resolution and 23 HLA alleles at a four-digit resolution associated with five antibodies, with eight HLA alleles associated with Epstein-Barr virus antibodies showing strong evidence of replication in UK Biobank. Our findings provide a useful resource for any future studies using the ALSPAC infection data and contributes to the understanding of the architecture of host genetics related to infections.